2015
DOI: 10.1016/j.jmmm.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic separation of algae genetically modified for increased intracellular iron uptake

Abstract: Algae were investigated in the past as a potential source of biofuel and other useful chemical derivatives. Magnetic separation of algae by iron oxide nanoparticle binding to cells has been proposed by others for dewatering of cellular mass prior to lipid extraction. We have investigated feasibility of magnetic separation based on the presence of natural iron stores in the cell, such as the ferritin in Auxenochlorella protothecoides (A. p.) strains. The A. p. cell constructs were tested for inserted genes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We recorded that the average amount of incorporated Tb 3+ per cell was 0.23 ± 0.0027 picogram (pg). This uptake of Tb 3+ is possibly due to detoxification mechanisms of the cells toward the nonessential/toxic Tb 3+ , as shown before for other positively charged ions like zinc or iron . In general, the uptake of positively charged ions takes place in two steps: the first is a rapid passive biosorption onto the cell wall to negatively charged functional groups, followed by a slow, energy consuming membrane transport .…”
Section: Resultsmentioning
confidence: 71%
“…We recorded that the average amount of incorporated Tb 3+ per cell was 0.23 ± 0.0027 picogram (pg). This uptake of Tb 3+ is possibly due to detoxification mechanisms of the cells toward the nonessential/toxic Tb 3+ , as shown before for other positively charged ions like zinc or iron . In general, the uptake of positively charged ions takes place in two steps: the first is a rapid passive biosorption onto the cell wall to negatively charged functional groups, followed by a slow, energy consuming membrane transport .…”
Section: Resultsmentioning
confidence: 71%
“…Simple overexpression of iron importers to increase intracellular iron concentrations is not the method of choice to magnetize cells. Free iron cations induce Fenton reactions and disturb iron homeostasis and show only little magnetic properties (Buck et al, 2015). Also the use of heme-proteins to magnetize cells seems to be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled import of iron without a specific intracellular recipient will likely result in disturbances in iron homeostasis (Crichton et al, 2002;Konhauser et al, 2011) and an increase in damaging Fenton reactions (Imlay, 2008;Yamada et al, 2012). However, we want to mention a recent study that showed successful magnetization of algae through overexpression of iron importers (Buck et al, 2015). Although separation of magnetic algae was demonstrated, the researchers highlighted this approach as economically unfeasible, due to low magnetization of algae.…”
Section: Proteins and Approaches For The Generation Of Imcs Iron Importersmentioning
confidence: 99%